Comparative simulation of crop productivity, soil moisture and nitrate-N leaching losses for intermediate wheatgrass and maize in Minnesota using the DSSAT model - Mulla, David J.; Tahir, Muhammad; Jungers, Jacob M. (Frontiers in Sustainable Food Systems, 2023)
Perennial grain crops are a potential alternative source of staple foods and animal forage that can also provide additional environmental benefits over annual crops. Intermediate wheatgrass (IWG; Thinopyrum intermedium) is a new perennial dual-use crop for grain and forage, with growing interest among stakeholders as it produces grain in a more environmentally sound manner than current annual crops. DSSAT model simulations were performed for maize and a new DSSAT model for IWG based on data collected from field studies conducted during 2013–2015 at three different locations, i.e., Lamberton, Waseca and Crookston using low (zero), medium (60–80 kg ha−1) and high fertilizer nitrogen (N) rates (120–160 kg ha−1). The DSSAT CERES-Maize and CROPGRO-PFM models used as the basis for simulating IWG were calibrated at the high N rate to predict the yield/biomass, soil water balance, and soil nitrogen balance in maize and IWG, respectively, for the medium and low N rate treatments. Model predictions for maize yield and IWG biomass (0.89 >= Nash Sutcliffe Efficiency >= 0.58), soil profile moisture (0.81 >=NSE>=0.53) ranged from very good to satisfactory for maize and the high N rate in IWG, with nearly satisfactory accuracy for IWG under the medium and zero N rates. Simulation results indicate that low, medium and high N rates produced an average IWG biomass of 7.8, 9.7, and 10.5 t ha−1, in addition to observed grain yield of 0.36, 0.49, and 0.45 t ha−1, respectively. The corresponding N rates produced 5.9, 7.9, and 8.7 t ha−1 maize yield. Soil profile moisture under IWG and maize averaged 0.25 and 0.29 m3m−3, respectively. Averaged over N rates and locations, IWG and maize had values for crop evapotranspiration (ETc) of 592 vs. 517 mm; deep percolation of 100.8 vs. 154.5 mm; and nitrate-N leaching losses of 2.6 vs. 17.9 kg ha−1, respectively. Results indicate that perennial IWG not only produced high biomass under rainfed conditions, but also reduced deep percolation by efficiently using soil profile moisture, leading to nitrate-N leaching losses six to seven times lower than for maize.